(untitled) (Nativa, 2023)
ABSTRACT: Common and medical plants were investigated for active biochemical to bind and inhibit the CYP51 protein in candida sp., 22 important plants were chosen and 263 molecular docking reactions were done between active materials and protein, 1441 different active ligands were detected for binding in protein active site, the best 225 ligands were chosen depending the power of affinity bond. Four ligands were candidates for having the best ligand affinity bond and more safety for use according to the toxicity test program; within these ligands, the Epicatechin was found to be the best biochemical for inhibition and bonding to CYP51 protein as it subjects to Lipinski’s rule of five. Keywords: molecular docking; medical plants; Candida sp. Investigação e identificação de alguns bioquímicos ativos em plantas medicinais contra a proteína CYP51 em candida usando Molecular Docking RESUMO: Plantas comuns e medicinais foram investigadas para bioquímicos ativos para ligar e inibir a proteína CYP51 em Candida sp., 22 plantas importantes foram escolhidas e 263 reações de docking molecular foram feitas entre materiais ativos e proteínas, 1441 ligantes ativos diferentes foram detectados para ligação em proteínas sítio ativo, o melhor ligante 225 foi escolhido dependendo do poder de ligação de afinidade. Quatro ligantes foram candidatos por ter melhor ligação por afinidade e maior segurança para uso de acordo com o programa de testes de toxicidade, dentro destes ligantes a Epicatequina mostrou ser o melhor bioquímico para inibição e ligação à proteína CYP51 por estar sujeita à regra dos cinco de Lipinski. Palavras-chave: docking molecular; plantas medicinais; Candida sp.